Post-Harvest Handling Practices Impacted on Microbiological and Sensory Quality Attributes of Giant Freshwater Prawn Macrobrachium Rosenbergii in the Distribution Chain in Bangladesh (Research in Agriculture Livestock and Fisheries, 2020)
To understand the effect of post-harvest good handling practices on prawn(Macrobrachiumrosenbergii) quality, data were collected from stakeholders involved indistribution chain by semi-structured questionnaire, focus group discussion and transectwalking at Kishoreganj and Mymensingh. Most used containers were split bamboo basket(39%), split bamboo basket with polythene lining (18%), plastic crate (12%), styrofoamcrate (8%) and rectangular metal container (12%). 15%, 25%, 10%, 100% and 7% largeprawns were water washed and 9%, 35%, 22%, 100%, 60% large prawns were icedimmediately after harvest, later in fishing trip, immediately after landing, at wholesalehouse before transportation and during retail sale, respectively. Bacterial counts of waterused for ice preparation, ice crushed mechanically and on soil floor collected from BhairabBazar and Karimganj were 6.58±1.87×103, 4.77±0.19×102, 4.12±2.06×103 cfu/ml and4.82±1.56×102, 6.01±1.61×101, 6.90±1.61×102 cfu/ml, respectively. Ice melted watercollected after unpacking prawn containers at Mymensingh, transported from BhairabBazar and Karimganj, had 5.90±1.95×107 and 6.32±2.06×108 cfu/ml bacterial counts,respectively; indicated unhygienic handling environments. However, existing post-harvesthandling practices produce prawns acceptable for consumers as sensory assessment forprawns showed the quality defect points of 1.0 (Excellent), 2.1 (Good), 2.3 (Good) and 2.9(Good) at harvesting, landing, wholesale and retail shop, respectively.Res. Agric., Livest. Fish.7(2): 321-328,  August 2020